Dynamic assessment of island ecological environment sustainability under urbanization based on rough set, synthetic index and catastrophe progression analysis theories. (1st August 2019) - Gao, Sheng; Sun, Huihui; Zhao, Lin; Wang, Runjie; Xu, Min; Cao, Guangxi
Abstract: An in-depth analysis of the main influencing factors affecting the island's ecological environment is an objective basis for accurately adjusting the island's development policies. It is of great significance to realize the coordination between island development and ecological environment. The dramatic development of Pingtan Island(PI) in the southeast coast of China has significantly impacted the survival environment. The ecological safety under island development and its driving factors should be evaluated. This paper extensively evaluates island ecological environment sustainability and builds a stress-state-response ecological environment sustainability evaluation index system that includes social economy and resource environment. This study develops a new progressive evaluation system based on the rough set, synthetic index and catastrophe progression theories. Highlights: The entropy weight method and rough set theory are used to construct the evaluation index system of ecological environment sustainability of Pingtan Island. The comprehensive index method and the catastrophe progression method is used to evaluate the ecological environment sustainability of Pingtan Island. The driving force analysis is performed by the path analysis method.